2020
DOI: 10.1002/cae.22297
|View full text |Cite
|
Sign up to set email alerts
|

Augmented and virtual reality for physics: Experience of Kazakhstan secondary educational institutions

Abstract: Currently, computer‐based training systems, such as virtual laboratories (VLs), are becoming more common not only in universities but also in secondary schools. For physics, VLs are of great importance, as they allow simulating processes that cannot be seen or reproduced. Technologies such as augmented reality (AR) and virtual reality (VR) help us to create such physical visualizations. This study presents a VL, which allows users to solve various physical practical tasks or problems with the help of three‐dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…Teaching mode is a teaching activity structure and teaching method constructed to achieve certain teaching objectives under the guidance of the theoretical and practical framework of learning environment design. It is an intermediary that transforms learning environment design theory into specifc teaching activity structures and operating procedures, and is the result of combining the design theory with a practical framework [25]. Generally, scholars in related felds include three orientations on teaching models, as expressed in Figure 2.…”
Section: An Analysis Of the Teaching Mode Of Children's Scientifc Qua...mentioning
confidence: 99%
“…Teaching mode is a teaching activity structure and teaching method constructed to achieve certain teaching objectives under the guidance of the theoretical and practical framework of learning environment design. It is an intermediary that transforms learning environment design theory into specifc teaching activity structures and operating procedures, and is the result of combining the design theory with a practical framework [25]. Generally, scholars in related felds include three orientations on teaching models, as expressed in Figure 2.…”
Section: An Analysis Of the Teaching Mode Of Children's Scientifc Qua...mentioning
confidence: 99%
“…Cai et al [40] and Chen et al [46] reported that students were able to enhance their flow experience when utilizing AR applications for learning about mechanics and astronomy. It should also be noted that students were more excited about applying smartphones on markers and observing visualizations, rather than watching the same animations on computers [49].…”
Section: Positive Effects On Affective Domain Of Learningmentioning
confidence: 99%
“…Liu et al (2010) explained that a higher level of consumer innovativeness makes them more acceptable and encourages them to experience novel technology, which helps them to develop positive beliefs about innovations. Daineko et al (2020) identified the essential factors that affect the growth and popularity of AR. These factors are interactivity, accessibility, realism and innovativeness.…”
Section: Innovativenessmentioning
confidence: 99%